Asertividad: problemas de definición y de medición -versión preliminar de una prueba- - Meza, Anibal (1984)
Relationships among non-assertion, timidness and social anxiety are commented firstly. Then, items of assessment devices on assertion are analyzed, stressing the fact that non-assertive answers cou Id beco me its contrary be cause of axiologic factors. From conceptual delimitations made throug hout, it comes that a) timidness is a personality trait; social anxiety and non-assertion are specific habits and behaviors included in it; b) nonassertion consists of an unbalancing condition on a kind of verbal interactions requiring overt expression of ideas ami feelings; e) social anxiety -evaluated by Willoughby lnventoryturns out to be a neurotic componen t. Analysis of formal and content aspects of Assertion lnventory by Rathus derive on lacks of consistency on how items were constructed and a doubtful content validity. Finally, and Assertion Test is proposed: its first section controls influence of axiologic factors, the second measures non-assertion per se and the third one allows information about non-verbal expressive factors. At presenta Research is being conducted for establishing validity and fiability sígns.